Tuning the excited-state deactivation pathways of dinuclear ruthenium(ii) 2, 2′-bipyridine complexes through bridging ligand design. Issue 24 (28th May 2020) - Cerfontaine, Simon; Troian-Gautier, Ludovic; Wehlin, Sara A. M.; Loiseau, Frédérique; Cauët, Emilie; Elias, Benjamin
Abstract : A detailed photophysical study of binuclear complexes was performed using steady-state and time-resolved photoluminescence measurements at variable temperature. The results were compared with the prototypical [Ru(bpy)3 ] 2+ . Abstract : A detailed photophysical investigation of two dinuclear ruthenium(ii ) complexes is reported. The two metallic centers were coordinated to a bis-2, 2′-bipyridine bridging ligand, connected either through the para (Lp, Dp ) or the meta position (Lm, Dm ). The results obtained herein were compared to the prototypical [Ru(bpy)3 ] 2+ parent compound. The formation of dinuclear complexes was accompanied by the expected increase in molar absorption coefficients, i.e. 12 000 M −1 cm −1, 17 000 M −1 cm −1, and 22 000 M −1 cm −1 at the lowest energy MLCTmax transition for [Ru(bpy)3 ] 2+, Dm and Dp respectively. The Lp bridging ligand resulted in a ruthenium(ii ) dinuclear complex that absorbed more visible light, and had a longer-lived and more delocalized excited-state compared to a complex with the Lm bridging ligand. Variable temperature measurements provided valuable information about activation energies to the uppermost 3 MLCT state and the metal-centered ( 3 MC) state, often accompanied by irreversible ligand-loss chemistry. At 298 K, 48% of [Ru(bpy)3 ] 2+ * excited-state underwent deactivation through the 3 MC state, whereas this deactivation pathway remained practically unpopulated (<0.5%) in both dinuclear complexes.